Associations between tactile localization and motor function in children with motor deficits. (15th March 2018) - Asano, Daiki; Morioka, Shu
Abstract : Children with developmental disorders often have poor motor performance. This study aimed to address the association between tactile localization ability, an indicator of body image, and motor function in children with motor deficits. Eighteen children with motor deficits participated, and their upper and lower limbs were assessed. To assess the level to which the patient's body image was developed, a tactile localization task (TLT) was used. In the TLT, experimenters touched a child's fingers, toes, or lower extremities (L/E), and the participants were asked to identify the location of the touch on a body part illustration. We compared TLT ability between high and low motor function groups, and investigated the correlation between TLT and the measures of motor function, age, and non-verbal intelligence. The high motor function group had significantly higher L/E TLT scores than the low motor function group, except in the tests involving the fingers and toes. Furthermore, the L/E TLT correlated only with motor function measures (Gross Motor Function Measure score, measured using one-leg standing time and one-leg hopping ability). The results suggest that children with motor deficits experience developmental delay in terms of their body image.